2020
DOI: 10.1017/s0033291720004055
|View full text |Cite
|
Sign up to set email alerts
|

Stigma resistance is associated with advanced stages of personal recovery in serious mental illness patients enrolled in psychiatric rehabilitation

Abstract: Background Stigma resistance (SR) is defined as one's ability to deflect or challenge stigmatizing beliefs. SR is positively associated with patient's outcomes in serious mental illness (SMI). SR appears as a promising target for psychiatric rehabilitation as it might facilitate personal recovery. Objectives The objectives of the present study are: (i) to assess the frequency of SR in a multicentric non-selected psychiatric rehabilitation SMI sample; (ii) to investigate the correlates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…Within our study, this desire, once contextualized is understood as a consequence of intolerance for troubled behavior. In line with previous recovery research, this genre confirms the significance of overcoming stigma ( 5 , 56 , 57 ) and regaining a sense of dignity ( 58 ) to develop a new, positive identity after being confronted with mental distress. A contextual approach, however, also showed the difficulty of this process for people that are deprived from the social and narrative resources to move beyond devaluating perceptions of mental distress.…”
Section: Discussionsupporting
confidence: 88%
“…Within our study, this desire, once contextualized is understood as a consequence of intolerance for troubled behavior. In line with previous recovery research, this genre confirms the significance of overcoming stigma ( 5 , 56 , 57 ) and regaining a sense of dignity ( 58 ) to develop a new, positive identity after being confronted with mental distress. A contextual approach, however, also showed the difficulty of this process for people that are deprived from the social and narrative resources to move beyond devaluating perceptions of mental distress.…”
Section: Discussionsupporting
confidence: 88%
“…Memory is one of the main dimensions highly correlated with executive functioning, which in turn, is closely related to stigma resistance. 72 Adequate executive functioning seems to promote adequate coping strategies, resilience, and those metacognitive abilities needed to fight against self-stigma as proposed in recent research. 72 This fact has been replicated in other studies such as that conducted by Grover et al, in which executive dysfunction was found to be significantly related to higher levels of self-stigma in people with schizophrenia.…”
Section: Discussionmentioning
confidence: 91%
“… 72 Adequate executive functioning seems to promote adequate coping strategies, resilience, and those metacognitive abilities needed to fight against self-stigma as proposed in recent research. 72 This fact has been replicated in other studies such as that conducted by Grover et al, in which executive dysfunction was found to be significantly related to higher levels of self-stigma in people with schizophrenia. 73 The conclusions obtained in these previous studies could explain the results of our work.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the controlling approach and the perception and treatment of the patient in an incompetent status remain in diff erent type of mental health care facilities. For example, if more attention is paid to strengths during rehabilitation, it will have an impact on the stigma associated with mental illness (Dubreucq et al, 2022) and, ultimately, on the severity of the symptoms of the illnesses. Sartorius' (1978) emblematic examination must be mentioned here which indicated that the clinical diagnosis on initial evaluation appeared to be a good predictor of subsequent symptomatology.…”
Section: Approach From Vulnerability To Abilitymentioning
confidence: 99%
“…Sartorius' (1978) emblematic examination must be mentioned here which indicated that the clinical diagnosis on initial evaluation appeared to be a good predictor of subsequent symptomatology. A recent study showed (Dubreucq et al, 2022) that stigma resistance is associated with advanced stages of personal recovery in serious mental illness patients. Challenging stigma through activism was associated with fewer depressive symptoms (Marcussen et al, 2021).…”
Section: Approach From Vulnerability To Abilitymentioning
confidence: 99%